Pool-Seq libraries of the 3 P. napi populations - Keehnen, Naomi L.P.; Hill, Jason; Nylin, Sören; Wheat, Christopher W. (Dryad Digital Repository, 2018)
Pool-Seq libraries of Spain: Aiguamolls, Sweden: Abisko, and Sweden: Kullaberg. Stored as NCBI bioproject PRJNA449143.